Assessing the performance of environmental management in academic research laboratories - Ladyman, Melissa K.; Gutierrez-Carazo, Encina; Persico, Federica; Temple, Tracey; Coulon, Frederic (Elsevier, 2022)
Managing environmental risk is essential to ensure organisations minimise their impact on the environment, comply with environmental legislation and maintain their reputation in an increasingly environmentally aware society. Organisations frequently use management systems to plan and execute routine environmental assessments, however environmental impacts may still arise from routine activities or accidents that could be avoided by effective environmental management. Currently there is no method for an organisation to assess the level of awareness their employees have of activities that may lead to an environmental impact, or the level of uptake of environmental management processes. Therefore, the Environmental Management Performance Assessment (EMPA) process was developed to enable organisations to self-assess existing environmental management processes by survey of their employees. The EMPA process was aligned to key phases of the Deming Cycle and involves development and distribution of a survey to organisation employees. The responses are then used to recognise areas for improvement by progression through a bespoke flow chart integrated with the initial survey. This enables demonstration of how particular hazards arise from insufficient awareness at different stages in the Deming Cycle and how these hazards can have wider, reputational, economic, and legislative consequences. The process was trialled by surveying academic researchers on the environmental management processes in their laboratories as a sample set.
Keywords: Environmental performance; Plan-do-check-act; Deming cycle; Environmental hazard; Environmental questionnaire